2018
DOI: 10.1007/s12192-018-0892-3
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cellular damage in tropical newly hatched sharks (Chiloscyllium plagiosum) under ocean acidification conditions

Abstract: Sharks have maintained a key role in marine food webs for 400 million years and across varying physicochemical contexts, suggesting plasticity to environmental change. In this study, we investigated the biochemical effects of ocean acidification (OA) levels predicted for 2100 (pCO ~ 900 μatm) on newly hatched tropical whitespotted bamboo sharks (Chiloscyllium plagiosum). Specifically, we measured lipid, protein, and DNA damage levels, as well as changes in the activity of antioxidant enzymes and non-enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 74 publications
3
18
0
Order By: Relevance
“…While the present findings align with other studies, that showed that several shark species appear to be somewhat resilient to OA (Heinrich et al, ; Johnson et al, ; Lopes et al, ; Pegado et al, ; Rosa et al, ), there was striking, albeit not statistically significant, reduction in the numbers of thrombocytes. Thus, the present study suggests that a long‐term exposure to high CO 2 translated in a tendency for a lower thrombocyte count.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While the present findings align with other studies, that showed that several shark species appear to be somewhat resilient to OA (Heinrich et al, ; Johnson et al, ; Lopes et al, ; Pegado et al, ; Rosa et al, ), there was striking, albeit not statistically significant, reduction in the numbers of thrombocytes. Thus, the present study suggests that a long‐term exposure to high CO 2 translated in a tendency for a lower thrombocyte count.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the scientific community started to investigate the effects that OA may have on sharks’ physiology and behavior (Green & Jutfelt, ; Heinrich et al, ; Rosa et al, ; Dixson, Jennings, Atema, & Munday, ; Heinrich et al, ; Pistevos, Nagelkerken, Rossi, Olmos, & Connell, ; Johnson, Kraver, Renshaw, & Rummer, ; Rosa, Pimentel, et al, ; Rosa, Ricardo, et al, ; Pistevos, Nagelkerken, Rossi, & Connell, ; Rosa, Rummer, & Munday, ; Lopes et al, ). Two studies have so far indicated the presence of compensation mechanisms in sharks exposed to OA.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no significant effects of either treatment were observed over hypoxia tolerance (Figure 6B; Supplementary Table 3), despite previous indication that these two responses may be intertwined (Butler and Taylor, 1975;Ely et al, 2014;Bouyoucos et al, 2020a). Likewise, cell stress levels, particularly oxidative damage, appear not to be affected by EA (Figure 6C; Supplementary Table 3), with elasmobranchs relying on non-enzymatic ROS-scavengers in addition to enzymatic antioxidants, which may be a potential explanation for their resilience (Lopes et al, 2018;Pegado et al, 2020a). However, this same response has rarely been addressed under EW and EWA, despite more evidence suggesting potentially considerable effects of these treatments over elasmobranchs and other taxa (Lesser, 2006;Rosa et al, 2016a).…”
Section: Tolerance and Stress Indicatorsmentioning
confidence: 80%
“…Heat Shock Protein 70 (HSP) were quantified in the supernatants of the homogenate and centrifuged glass eels' remaining body through ELISA, as described in Lopes et al (2018). In sum, 10 μL of sample diluted in 980 μL PBS was added to 96-well microplate (Microlon 600, Greiner, Austria) and allowed to incubate overnight at 4 • C. On the next day, microplates were washed three times with PBS TWEEN-20 (0.05%).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%